Arabicfy Application As A Mufrodat Learning Media For Class IV Students Of SDIT Al-Amanah Islamic School Lembang - Naqiyah, Neni; Shalihah, Imroatus; Ferdiansyah, Novan; Handayani, Latifah; Huda, Miftahul; Machmudah, Umi (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
In the increasingly advanced digital era, the urgency of using technology-based learning media in the world of education is becoming increasingly important, including in learning Arabic in elementary schools, especially in mufrodat learning. This research aims to determine the steps for using the Arabicfy application and evaluate the effectiveness of using Arabicfy as a mufrodat learning medium. The method used in this research is mixed methods which combines a qualitative approach and a quantitative approach. The results of this research include 1) steps for using the Arabicfy application in learning mufrodat which consists of seven steps, namely: first, download the Arabicfy application. Second, open the Arabicfy application. Third, select the user guide menu. Fourth, select the table of contents menu. Fifth, the teacher explains the learning objectives to students. Sixth, the teacher presents vocabulary material. Seventh, the teacher evaluates students. 2) The Arabicfy application is very effective as a mufrodat learning media with a percentage of 52% of students liking learning Arabic vocabulary using Arabicfy media, 85% of students finding it easy to understand and memorize the mufrodat given by the teacher, and 74% of students are very interested in working on it. Questions are given by the teacher.   Keywords: Arabicfy Application, Learning Media, Mufrodat